PENETAPAN UKURAN SASARAN SEBAGAI USAHA PENINGKATAN EFISIENSI PROSES PENGGERGAJIAN - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Two units of sawmill in Lampung (Sumatera) and three units in West-Java have been visited for the purpose of this study. Determination of target size on each sawmill was firstly done by collecting data from thickness measurements of 100 board samples. The data was then calculated using the most common formulas used for determining the lumber target size.The result of the study revealed that actual size produced by two sawmills surveyed were higher than target size, ranging from 1.08 to 1.58 mm. The actual size from three other sawmills were lower than target size, ranging from 0.26 to 2.18 mm. The sawmill A has apparently the best sawing capability. This was indicated by the smallest thickness range either within or between board i.e. 0.89 mm and 0. 79 mm. Meanwhile, its total sawing variation was smallest i.e. 0.49 mm.The result of this study was an indication that there is a need for improving the efficiency of sawing process through the application of target size determination.